Locomotion gait pattern development for quadruped walking robot - Farahiyah binti Jasni (Kulliyyah of Engineering, International Islamic University Malaysia, 2013)
The earth, in many areas is hardly reachable by the use of wheeled or tracked robot. Thus, legged or walking locomotion mechanism is needed to widen the area that the machine can explore. However, the locomotion gait pattern development and control is always a challenging task in designing the legged robot because of its complexity. The common approach used is by pre-designing the trajectory of the foot or the body and that trajectory is used to obtain the parameters needed to move the robot, such as the joint angle values. This thesis proposed a hybrid method combining the biologically inspired method, Van Der Pol-Central Pattern Generator (VDP-CPG) and the conventional trajectory based method to generate the gait for the quadruped robot. Instead of having to derive and generate the trajectories of the foot or the body every time, the method proposed in this thesis is making use of the biological inspired method called the VDP-CPG method to generate the 3D foot trajectories of the robot. The advantage of using the VDP-CPG method is it offers easier approach in changing the gait pattern by only modulating the VDP-CPG parameters. The simulation procedures are designed, executed and compared to the pre-designed path trajectory method, the Composite Cycloid Function, to check the performance of the proposed method. The hardware experimentation are then performed the efficacy of the designed algorithm. Generally, the results show that the proposed method is comparatively good and practicable as compared to the benchmark method. However, this research work is limited to development of the walking gait only. This research work has proved that the hybrid method proposed is a good platform to start for the development of an adaptive locomotion system for the walking robot that can change the gait depending on the nature of the terrain for its ability to generate the trajectories by only modulating some parameters.